Brucellosis and the respiratory system - Pappas, Georgios; Bosilkovski, Mile; Akritidis, Nikolaos; Mastora, Maria; Krteva, Liliana; Tsianos, Epaminondas (Oxford University Press (OUP), 2003)
Brucellosis is a zoonotic disease that remains endemic worldwide. Its clinical manifestations and focal complications are often troublesome in making a diagnosis. Involvement of the respiratory system in brucellosis is an acknowledged but rare event that is only occasionally described in literature. We describe 37 cases of respiratory involvement during the course of brucellosis that presented as pneumonia, bronchopneumonia, pleural effusion with a predominance of monocytic or lymphocytic infiltrates, and paroxysmal dry cough. We also discuss aspects of the respiratory pathology, radiological characteristics, coexisting complications, and aspects of treatment of respiratory brucellosis.